Variables affecting new drug prices in South Korea’s pricing system - Lee, Dong Yun; Cho, Seong Ha; Lee, Da Hye; Kang, Su Jeong; Lee, Jong Hyuk (Frontiers in Pharmacology, 2024)
Objective: The price of pharmaceuticals is important from the economic and industrial perspectives but as well as patients’ access to treatment. This study aimed to analyze the variables affecting the prices of new drugs in South Korea’s pricing system. Methods: Data on 192 new drugs listed in South Korea from 2012–2022 were collected from the official website of the Health Insurance Review and Assessment Service. The independent variables included drugs for severe diseases, alternatives, number of patients, number of advanced 7 countries listed, budget impact, and listing period. The dependent variables included annual treatment cost and the price ratio to the advanced 7 country’s average adjusted price. Descriptive statistics of variables, linear correlations between quantitative independent and dependent variables, and associations between independent and dependent variables were analyzed. Results: The mean annual treatment cost and price ratio to the advanced 7 country’s average adjusted price were higher for drugs for severe diseases and those with no alternatives. Annual treatment cost and price ratio to the advanced 7 country’s average adjusted price were negatively correlated with the number of patients and positively correlated with the number of advanced 7 countries listed. Annual treatment cost was affected by the variables drugs for severe diseases, alternatives, number of patients, number of advanced 7 countries listed, and budget impact. The price ratio to the advanced 7 country’s average adjusted price was affected by drugs for severe diseases, alternatives, and the number of patients. Conclusion: This study revealed the effect of different variables on the prices of new drugs in South Korea, allowing for the development of a more effective assessment system to evaluate the prices of new drugs while ensuring profitability for pharmaceutical companies, sustainability of public insurance, and accessibility to drugs by patients.